Design of a Thiosemicarbazide-Functionalized Calix[4]arene Ligand and Related Transition Metal Complexes: Synthesis, Characterization, and Biological Studies - Bahojb Noruzi, Ehsan; Kheirkhahi, Mahsa; Shaabani, Behrouz; Geremia, Silvano; Hickey, Neal; Asaro, Fioretta; Nitti, Patrizia; Kafil, Hossein Samadi (Frontiers in Chemistry, 2019)
In this study, we synthesized a new thiosemicarbazide functionalized calix[4]arene, L and its Co2+, Ni2+, Cu2+ and Zn2+ transition metal complexes. For characterization several tecniques were employed: FT-IR, 1H-NMR, 13C-NMR, 15N-NMR, COSY, NOESY, ESI-Mass spectroscopy, SEM, EDS, and elemental analysis. To explore the capability of the thiosemicarbazide function hosted on a calix[4]arene scaffold for growth inhibition of bacteria, fungi and cancerous tumor cells, a series of biological evaluations were performed. For L, the antimicrobial tests revealed a higher antibacterial activity against gram positive B. subtilis and a lower activity against gram-negative bacteria (E. coli and P. aeruginosa) while the gram positive S. aureus shows resistance. All examinated metal derivatives show an enhancement of the antibacterial activity against gram-negative bacteria, with a more significant improvement for the Cu2+ and Zn2+ complexes. MTT assays showed considerable in vitro anticancer activity of Co2+, Ni2+ and Cu2+ complexes against Saos-2 bone cancer cell lines. Activity ascribables to the inorganic ions rather than calixarene ligand. Hemolysis assay results demonstrated that all compounds have high blood compatibility.